PECULIARITIES OF FORMATION OF THE EUBACTERIAL COMPLEX OF WINTER WHEAT RHYSOPHERE (TRITICUM DURUM) BY DIFFERENT FERTILIZATION SYSTEMS - HUDZ, S.; SKIVKA, L. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
The of the study was to determine the quantitative, qualitative composition and taxonomic structure of the eubacterial complex in the rhizosphere of winter wheat using different fertilizer systems.Methods.Microbiological methods were used to determine the content of winter microorganisms in the wheat rhizosphere, and molecular taxonomic structure and methane of the eubacterial complex of microorganisms were determined. Results.It was found that among large phyla on the variants of the biological system of winter wheat fertilizer the share of Proteobacteria increased to 80,3 %, and the number of Actinobacteria decreased to 12.4% according to the control variant 76,3 and 17,5 %, also similar growth rates were marked on the variant of the ecological fertilizer system. The analysis of families shows that such families as Alcaligenaceae and Pseudomonadaceae were dominant in winter wheat crops with the use of different fertilizer variants. Under the industrial fertilizer system, the share of the family Alcaligenaceae was the highest, but with the application of biological and ecological systems it decreased, while the prevalence of the family Pseudomonadaceae on the contrary – increased. The use of organic fertilizers, compared with mineral, contributed to the formation of a variety of bacteria, so the greatest diversity of prokaryotes according to the Shannon index was in the biological fertilizer system – 4,82, and the least – in the industrial version of winter wheat fertilizer. Conclusions. It was found that in the variant of the biological fertilization system the increase of species diversity was due to the following phyla: Acidobacteria, Actinobacteria, Bacteroidetes, Firmicutes, Proteobacteria, Verrucomicrobia, and in the ecological fertilization system due to such philos as: Actinobacteria, Bacteroidetes, Firmicutes and Proteobac. In general, according to the experiment, the absolute dominants were representatives of bacterial philosProteobacteria – 79,1 %, Actinobacteria – 14,0 %.